Synthesis, structure, spectral, electrochemical and sensing properties of 3-amino boron-dipyrromethene and its derivatives - Ganapathi, Emandi; Madhu, Sheri; Chatterjee, Tamal; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Dyes and Pigments, 2014)
We report the synthesis of 3-amino boron-dipyrromethene (3-amino BODIPY) by treating 3-bromo boron-dipyrromethene (3-bromo BODIPY) initially with sodium azide in acetonitrile followed by tri-phenylphosphine(PPh3)/H2O in tetrahydrofuran in three steps under mild reaction conditions. In this reaction, 3-azido BODIPY which formed in the first step was not isolated but the 3-iminophosphorane BODIPY which formed in the second step was isolated and characterized crystallographically. The 3-amino BODIPY was characterized by various spectroscopic and X-ray analytical techniques. To test the reactivity of amine functionality on BODIPY core, we prepared 1-(meso-anisyl BODIPY)-3-phenyl urea/thiourea derivatives under simple reaction conditions. Our studies indicated that 1-(meso-anisyl BODIPY)-3-pheny thiourea can act as specific chemodosimetric sensor for Hg2+ ion and 1-(meso-anisyl BODIPY)-3-phenyl urea as colorimetric and ratiometric sensor for F- ion. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: 3-Amino boron dipyrromethene; Chemodosimeter; F sensor; Fluorescent probes; Iminophosphorane BODIPY; Mercury(II) sensor